Indications for hyperthermic intraperitoneal chemotherapy with cytoreductive surgery: a systematic review. (March 2020) - Auer, Rebecca C.; Sivajohanathan, Duvaraga; Biagi, Jim; Conner, James; Kennedy, Erin; May, Taymaa
Abstract: The purpose of the present review was to describe evidence-based indications for hyperthermic intraperitoneal chemotherapy (HIPEC), with cytoreductive surgery (CRS), in patients with a diagnosis of mesothelioma, appendiceal (including appendiceal mucinous neoplasm), colorectal, gastric, ovarian or primary peritoneal carcinoma. Relevant studies were identified from a systematic MEDLINE and EMBASE search of studies published from 1985 to 2019. Studies were included if they were RCTs. If no RCTs were identified, prospective and retrospecctive comparative studies (where confounders are controlled for studies with greater than 30 patients) were included. Overall survival, progression-free survival, recurrence-free survival, adverse events and quality of life data were extracted. For patients with newly diagnosed, primary stage III epithelial ovarian, fallopian tube or primary peritoneal carcinoma, HIPEC with CRS should be considered for those with at least stable disease following neoadjuvant chemotherapy at the time of interval CRS if complete or optimal cytoreduction is achieved. There is insufficient evidence to recommend the addition of HIPEC when primary CRS is performed for patients with newly diagnosed, primary advanced epithelial ovarian, fallopian tube or primary peritoneal carcinoma or in those with recurrent ovarian cancer outside of a clinical trial. There is insufficient evidence to recommend HIPEC with CRS for the prevention of or for the treatment of peritoneal colorectal carcinomatosis outside of a clinical trial. There is insufficient evidence to recommend HIPEC with CRS for the prevention of or for the treatment of gastric peritoneal carcinomatosis outside of a clinical trial. There is insufficient evidence to recommend HIPEC with CRS in patients with malignant peritoneal mesothelioma or in those with disseminated mucinous neoplasm in the appendix as a standard of care; however, these patients should be referred to HIPEC specialty centres for assessment for treatment as part of an ongoing research protocol.